Effect of irrigation on grain sorghum ethanol yield and sorghum mutants on biomass composition - Pang, Bairen (Kansas State University, 2017)
Bioprocessing is widely involved in our daily life and significantly relative to the general public because bio-products are widely used in eating, clothing, and living as well as transportation. Due to the public concern of the environmental deterioration, limited fossil fuel resources, and energy price volatility, biofuel as a clean, safe and sustainable energy needs to be developed in response to this growing concern. Sorghum, an important dryland crop, represents a renewable resource currently grown on 8 million acres throughout the United States. Due to climate variability and the continuous decline of water resources, utilization of dryland to grow sorghum and forage sorghum is critically important in order to ensure available energy resources and sustainable economic development. The objectives of this research were 1) to study the impact of deficit irrigation strategies on sorghum grain attributes and bioethanol production, and 2) to evaluate the potential fermentable sugar yield of pedigreed sorghum mutants. Results showed that average kernel weight and test weight of grain sorghum increased as irrigation capacity increased, whereas kernel hardness index decreased as irrigation capacity increased. Starch content increased as irrigation level increased and protein contents decreased as irrigation level increased. Irrigation also had a significant effect on starch properties and bioethanol yield. Sorghum mutants had a significant effect on chemical composition and physical properties such as glucan content, glucan mass yield, ash content, and high heating value, and also had a significant effect on fermentable sugars yield and enzymatic conversion efficiency.
Keywords: Sustainable energy; Biofuel; Deficit irrigation; Bioethanol yield; Sorghum mutant biomass; Starch content